Mapping the Evolution of Agricultural Economics: A Bibliometric Analysis of the Nexus Between Economic Growth, Environmental Sustainability, and Econometric Modeling - Qalbin Salim Fazli; Mussa Isaack Delya; Muhammad Akbar Almuchty; Iffah Hafizah; Dimas Bagus Wiranatakusuma (Ekonomikalia Journal of Economics, 2025)
Understanding how agriculture contributes to economic growth while maintaining environmental sustainability has become an essential question in contemporary development research. To examine how this interdisciplinary field has evolved, this study employs a bibliometric analysis of 394 Scopus-indexed articles retrieved on 3 October 2025, reflecting research published from 1975 through 2025, focusing on the intersection of agriculture, economic growth, environmental sustainability, and econometric modeling. Data were analyzed with VOSviewer and CiteSpace to map research trends, collaboration, and methodological patterns. The results indicate a consistent rise in publication activity and citation impact, reflecting the growing scholarly attention to sustainable agricultural economics. Asian countries, particularly China, India, Malaysia, and Indonesia, have emerged as leading contributors, highlighting the region’s central role in agricultural transformation and policy-driven research. Econometric approaches such as time series, panel data, and cointegration models dominate methodological trends, underscoring the discipline’s increasing reliance on quantitative analysis. However, international and interinstitutional collaboration remains limited, suggesting that greater integration is needed to achieve a more unified global research landscape. The findings provide valuable insights into the intellectual structure and evolution of agricultural economics, offering a foundation for future studies that aim to strengthen methodological diversity and advance sustainable development policies.